Countering culture: religious motivation and adherence to the "inmate code" - Wiernik, Craig S. (The journal of religion & society, 2013)
Does religion have an impact on a prison inmate's behavior? This paper reports the results of a study that shows that an inmate's motivations for appearing to be religious in prison is a better way to understand the association between religion and their future behavior. Using data from a number of prisons in the United States and multinomial-logistic regression, I show that an inmate's intrinsic motivations for pursuing religion impact the inmate's behavioral intentions in a variety of social situations in prison, and that this inmate's actions would "stand out" from fellow inmates' actions in ways that run contrary to the inmate code, when compared to those inmates who pursue religion for the extrinsic benefits.